The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.cub.2016.09.057
|View full text |Cite
|
Sign up to set email alerts
|

Recall of Others’ Actions after Incidental Encoding Reveals Episodic-like Memory in Dogs

Abstract: The existence of episodic memory in non-human animals is a debated topic that has been investigated using different methodologies that reflect diverse theoretical approaches to its definition. A fundamental feature of episodic memory is recalling after incidental encoding, which can be assessed if the recall test is unexpected [1]. We used a modified version of the "Do as I Do" method [2], relying on dogs' ability to imitate human actions, to test whether dogs can rely on episodic memory when recalling others'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 38 publications
2
51
0
8
Order By: Relevance
“…Among others, it was shown that dogs are capable of social learning (e.g. Pongrácz et al 2001), including various instances of imitation where in some specific cases we have convincing evidence for imitating novel actions through episodic memory as well (Fugazza et al 2016). Dogs not only have a given identity, but they are also able to recognize their own names, even amidst distracting verbal background noise (Mallikarjun et al 2019).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Among others, it was shown that dogs are capable of social learning (e.g. Pongrácz et al 2001), including various instances of imitation where in some specific cases we have convincing evidence for imitating novel actions through episodic memory as well (Fugazza et al 2016). Dogs not only have a given identity, but they are also able to recognize their own names, even amidst distracting verbal background noise (Mallikarjun et al 2019).…”
Section: Introductionmentioning
confidence: 75%
“…Thus, it is reasonable to assume that dogs may possess a complex enough mental representational system and also an ecologically valid need for at least some form of representing the self. In the case of dogs, there were sporadic efforts where some components of self-representation were tested, such as the presence of episodic-like memory (Fugazza et al 2016). It was another approach, when they investigated the ability of the discrimination of own odor from others' (Bekoff 2001;Gatti 2016;Horowitz 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Il s'agit donc d'une mémoire à long terme du « quoi ». Ils sont ainsi capables d'imiter une action, réalisée par un homme (par exemple, toucher une cible avec le nez), et de la reproduire sur commande, quelques minutes, voire une heure, après la démonstration [23][24][25]. Au-delà du critère de durée, la mémoire à long terme est subdivisée en deux sous-types de mémoire : la mémoire explicite (ou déclarative), qui correspond au souvenir conscient.…”
Section: Les Mécanismes De Mémorisationunclassified
“…Le premier est l'absence d'encodage actif de l'information durant la phase d'exposition à l'événement : le sujet ne cherche pas, de façon active, à se rappeler ce qui vient de se passer. La nature accidentelle, accessoire, de la mémorisation est une propriété essentielle pour parler de mémoire épisodique [24,42]. Le second critère est que le sujet se rappelle de l'événement en l'intégrant dans son autobiographie « qui, quoi et quand ?…”
Section: Le Chien Comme Modèle D'étude ?unclassified
“…This new field has given rise to studies that show dogs may be comparable with humans in tasks involving learning and memory, especially complex memory types such as episodic memory (Fugazza, Pogány, & Miklósi, 2016). It is even suggested that dogs may be an ideal animal model for the study of human agerelated diseases affecting memory, such as Alzheimer's and dementia (Cummings, Head, Ruehl, Milgram, & Cotman, 1996).…”
mentioning
confidence: 99%